Central muscarinic receptor subtypes involved in pilocarpine-induced salivation, hypertension and water intake - Borella, T. L. [UNESP]; De Luca, L. A. [UNESP]; Colombari, Débora Simões de Almeida [UNESP]; Menani, José Vanderlei [UNESP] (Wiley-Blackwell, 2008)
Background and purpose: Recent evidence has suggested that pilocarpine (ACh receptor agonist) injected peripherally may act centrally producing salivation and hypertension. In this study, we investigated the effects of specific M(1) (pirenzepine), M(2)/M(4) (methoctramine), M(1)/M(3) (4-DAMP) and M(4) (tropicamide) muscarinic receptor subtype antagonists injected into the lateral cerebral ventricle (LV) on salivation, water intake and pressor responses to peripheral pilocarpine.Experimental approach: Male Holtzman rats with stainless steel cannulae implanted in the LV were used. Salivation was measured in rats anaesthetized with ketamine (100mg per kg body weight) and arterial pressure was recorded in unanaesthetized rats.Key results: Salivation induced by i.p. pilocarpine (4 mu mol per kg body weight) was reduced only by 4-DAMP (25-250 nmol) injected into the LV, not by pirenzepine, methoctramine or tropicamide at the dose of 500 nmol. Pirenzepine (0.1 and 1 nmol) and 4-DAMP (5 and 10 nmol) injected into the LV reduced i.p. pilocarpine-induced water intake, whereas metoctramine (50 nmol) produced nonspecific effects on ingestive behaviours. Injection of pirenzepine (100 nmol) or 4-DAMP (25 and 50 nmol) into the LV reduced i.v. pilocarpine-induced pressor responses. Tropicamide (500 nmol) injected into the LV had no effect on pilocarpine-induced salivation, pressor responses or water intake.Conclusions and implications: The results suggest that central M(3) receptors are involved in peripheral pilocarpine-induced salivation and M(1) receptors in water intake and pressor responses. The involvement of M(3) receptors in water intake and pressor responses is not clear because 4-DAMP blocks both M(1) and M(3) receptors.
Keywords: muscarinic receptors; M(1) and M(3) receptors; salivary glands; arterial pressure; thirst